قضايا المرأة في تفسيري الواحدي وابن عاشور دراسة منهجية مقارنة - مطرفي، صالحة حويض (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2017)
The study deals with the most important aspect related to the issue of Muslim woman coined by Imam al-Wahidi and IbnAshur within their books of tafsir (al-Basit and al-Tahrir wa al-Tanwir). It elaborates the used methods of giving exposition toward the verses related to woman issue by focusing on similarities and differences. Some aspects which becomes the main focus of the study is to reveal the biography and educational and cultural background, the scholarly works and salient features of tafsir al-Basit and al-Tahrirwa al-Tanwir. Moreover, it also discusses some examples related to woman issue such as monthly period, post anti natal, the right and obligation of husband and wife, different types of divorce, the issue of wearing scarves, and the wisdom behind polygamous marriage. The other significant part of the study discusses methodological comparison used by al-Wahidi and IbnAshur in dealing with woman issue which primarily focuses on the differences and similarities of the methods. The researcher came out with important findings in which Imam al-Wahidi in elaborating the verses related to woman issue mostly refers to the classical data resource which mainly comes from the views of companions and successors (al-tabiin). In addition, he supports the argument by referring to the causes of sending down of the revelation (asbab al-nuzul). IbnAshur in discussing the woman issue apart from the emphasis on grammatical and rhetorical point of view, he relates the meaning of verses with the reality of life which deals with the issue of Muslim women in the society. The other important parts is that IbnAshur refers to the sources which deals with the scientific fact pertains to the issue of Muslim woman. The methodological comparison, the researcher found ten similarities and differences between al-Wahidi and IbnAshur as discussed in detail within the study. There are some other areas which need to be studied further which are related to another issuesuch as theological, jurisprudential and linguistic aspects.